Prinsip Non-Kooperasi Soekarno sebagai Komunikasi untuk Melawan Kolonialisme - Fidelis Aggiornamento Saintio; Anang Sujoko; Wawan Sobari (Universitas Merdeka Malang, 2021)
Colonialism is closely related to monological, stereotypical, and hegemonic communication patterns. This implies a superior and inferior dichotomy between colonizer and colonized. The colonized nation which was labeled inferior in the end tended to imitate (mimicry) the colonizer, who claimed to be superior. One of the efforts made by Soekarno to counter this was by using the principle of non-cooperation. As a principle, non-cooperation is used to generate the nation's independence, self-confidence and national identity. This study uses hermeneutic analysis to explore a more comprehensive meaning of the non-cooperation principle. The main focus of this research is to find out the authentic values ​​which are the result of applying the principle of non-cooperation. The results of this study indicate that non-cooperation does not only revolve around reluctance to cooperate, mass action, and revolution. Soekarno used the principle of non-cooperation as a form of communication to construct alternative narratives that could be used against colonialism. In the end, non-cooperation also grows the seeds of the formulation of a national personality that can be used as a guideline for shaping national identity.Keywords: Colonialisme, Soekarno, Non-Cooperation, Hegemony, National IdenityDOI : https://doi.org/10.26905/nomosleca.v7i1.5336